The Greek gods - Evslin, Bernard; Hoopes, Ned.; Evslin, Dorothy; Hunter, William (New York : Scholastic, 1966)
A collection of classic legends of the Greek gods.
6.0
7-10
840
Keywords: Mythology, Greek -- Juvenile literature; Mythology, Classical; Mythology, Greek